2016
DOI: 10.1002/mnfr.201600552
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in cardiometabolic risk factors by a multifunctional diet is mediated via several branches of metabolism as evidenced by nontargeted metabolite profiling approach

Abstract: The metabolomics approach revealed that consumption of MFD affected different areas of metabolism, highlighting the impact of a healthy diet on plasma metabolome. This seems linked to reduced cardiometabolic risk and provides mechanistic insight into the effects of MFD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 32 publications
4
29
1
Order By: Relevance
“…We also found a putative marker of fish intake, CMPFP, to be associated with lower odds of CD. There is a large epidemiological literature linking fish consumption to lower CD and although CMPFP did not significantly correlate with fish intake in our sample, CMPFP was found increased after consuming fish‐rich Mediterranean and Nordic diets in two untargeted metabolomics studies, and was recently confirmed as a potential biomarker of fish . Moreover, we found an unidentified ion highly correlated with (red) wine intake, to be associated with lower odds of CD.…”
Section: Discussioncontrasting
confidence: 58%
“…We also found a putative marker of fish intake, CMPFP, to be associated with lower odds of CD. There is a large epidemiological literature linking fish consumption to lower CD and although CMPFP did not significantly correlate with fish intake in our sample, CMPFP was found increased after consuming fish‐rich Mediterranean and Nordic diets in two untargeted metabolomics studies, and was recently confirmed as a potential biomarker of fish . Moreover, we found an unidentified ion highly correlated with (red) wine intake, to be associated with lower odds of CD.…”
Section: Discussioncontrasting
confidence: 58%
“…This observation is in line with the reported beneficial effects of Lovaza on regulation of lipid profiles in humans, suggesting that CMPF may be an active component of FO, contributing to the beneficial metabolic effects seen in humans. Interestingly, human studies have also revealed a strong correlation between elevated circulating CMPF and reduced plasma TG levels, associating CMPF with a role in regulating glycolipid metabolism …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, human studies have also revealed a strong correlation between elevated circulating CMPF and reduced plasma TG levels, associating CMPF with a role in regulating glycolipid metabolism. [14][15][16] Mechanistically, CMPF was found to be an inhibitor of acetyl-coA carboxylase (ACC), the master regulator of fatty acid metabolism, as well as having the ability to induce the production of fibroblast growth factor 21 (FGF21). 9 CMPF's long-term preventive effect on HFDinduced hepatic lipid accumulation is absent in FGF21KO mice, suggesting that the long-term beneficial effect of CMPF on metabolism is FGF21 dependent.…”
mentioning
confidence: 99%
“…In previous studies, we have observed improved cardiometabolic markers in healthy at-risk individuals after 4–8 week intake of MFD targeting low-grade inflammation [7, 8]. The diet exerted also extensive impact on the plasma metabolome, particularly the lipidome [9]. However, whether these improvements can be associated with changes in the gut microbiota composition has not been investigated.…”
Section: Introductionmentioning
confidence: 99%